Morphosemantic fields in the analysis of Croatian vocabulary - Raffaelli, Ida; Kerovec, Barbara (2008)
This paper presents the morphosemantic field model, claiming that it is relevant in the description of lexical structures in grammatically-motivated languages such as Croatian. Arguments are presented for the applicability of the model in synchronic and diachronic lexical analysis. The fact that many characteristics of morphosemantic fields are compatible with the theoretical framework of cognitive linguistics is given special attention. It is argued that morphosemantic fields are highly relevant to diachronic research of lexical structures, because they enable the detection and definition of semantic and conceptual shifts and links through time.
Projekt MZOS
ENG